Permanent human canines: their importance for dental anatomy teaching - Genaro, Luis Eduardo; Marconato, José Victor; Conte, Marcelo Brito; Capote, Ticiana Sidorenko de Oliveira (Brazilian Journal of Implantology and Health Sciences, 2023)
Objectives: Permanent canines have an important functional role during mastication due to their anatomy,cbesides its relevance in oral esthetics. However, dentistry undergraduates have great difficulty in differentiating them during dental anatomy classes. The objective of this work was to study the morphology of the extracted permanent maxillary canines (MC) and lower canine (LC) in order to describe the anatomical similarities and differences. Methods: One hundred maxillary canines and 100 lower canines were evaluated. Measurements were performed using a digital caliper, and also visual analysis. The data obtained in each evaluation were submitted to descriptive statistical analysis, and the chi-square test and Fisher's exact test with a significance level of 5% were applied. Results: It was observed that the MC root groove was present on the two proximal surfaces and the groove depth was greater on the mesial surface, as reported in the literature. The MC incisal ridge was normally worn, and imprecision in dental differentiation could occur during the anatomical study, while it is stated that the incisal ridge allows distinguishing this tooth by a simple visual examination. The marginal ridges of the MC had a moderate prominence, as observed in the literature. The MC cingulum often presented a moderate prominence, contradicting some studies which reported a large cingulum. The presence of the cervicoincisal ridge on the lingual surface was frequently observed with moderate, absent or little prominence, while some authors reported that this structure is quite evident. Furthermore, it is reported that MC usually presents a foramen cecum, which was not observed in our sample. LC often presented a worn incisal ridge. The cingulum, marginal ridges, lingual fossa and developmental grooves were less evident and, in some cases, the lingual surface presented a flat shape, which is not usually reported in the literature. Conclusions: The morphological differences and similarities of MC and LC are important for a detailed anatomical study to help dentistry undergraduates identify them correctly. Furthermore, the anatomical study is important for the restorative area for an appropriate aesthetics and function rehabilitation.